2020
DOI: 10.1002/trc2.12084
|View full text |Cite
|
Sign up to set email alerts
|

The potential for one drug, administered at the earliest preclinical stage, to prevent the subsequent decline of cognition that eventuates in dementia

Abstract: In the process that eventuates in mild cognitive impairment (MCI) and ultimately in Alzheimer's dementia, the earliest identifiable change is in the function of synapses. If started at that early point in time, when there is subjective but not objective memory loss plus abnormal brain imaging with fluorodeoxyglucose and Pittsburgh compound B, treatment with a single drug directed at synaptic dysfunction might prevent development of cognitive impairment. Each of four drugs, dantrolene, lithium, minocycline, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…49 Those high levels of Ca 2+ may be prevented by dantrolene, discussed in detail in Fessel. 3 Finally, and of note, Mattiason et al showed that mitochondria isolated from the hippocampal CA1 region are more susceptible to an excessive Ca 2+ load than are mitochondria isolated from the CA3 region, 50 which is relevant in the present context because CA1 is more important than is CA3 for memory and cognition.…”
Section: Calcium and Magnesium Involvement In Atp Formation; The Crit...mentioning
confidence: 88%
See 3 more Smart Citations
“…49 Those high levels of Ca 2+ may be prevented by dantrolene, discussed in detail in Fessel. 3 Finally, and of note, Mattiason et al showed that mitochondria isolated from the hippocampal CA1 region are more susceptible to an excessive Ca 2+ load than are mitochondria isolated from the CA3 region, 50 which is relevant in the present context because CA1 is more important than is CA3 for memory and cognition.…”
Section: Calcium and Magnesium Involvement In Atp Formation; The Crit...mentioning
confidence: 88%
“…Further, extrusion of excessive Ca 2+ requires ATP and causes its further depletion 49 . Those high levels of Ca 2+ may be prevented by dantrolene, discussed in detail in Fessel 3 . Finally, and of note, Mattiason et al.…”
Section: Calcium and Magnesium Involvement In Atp Formation; The Crit...mentioning
confidence: 99%
See 2 more Smart Citations